Penggunaan Rangkaian Filtrasi FM2FV untuk Menurunkan Kadar Kekeruhan dan Coliform Air Hujan di RS Bethesda Yogyakarta Tahun 2012 - Fransisca Widiana Arimawanti; Lucky Herawati; F. X. Amanto Rahardjo (Sanitasi: Jurnal Kesehatan Lingkungan, 2013)
Rainwater is one of the most potential sources for water supply which can be used for everydaypurposes, including in hospitals. Rainwater relatively has good quality, however, in the harvesting process, i.e. by collecting the water pouring from the roof, pollutants may be brought andaffecting the quality of the rainwater. Filtration by using multimedia filter and ultraviolet disinfection (FM2FV) prior to the use of rainwater is one effort that can be applied to tackle that problem.The study was held in Bethesda Hospital of Yogyakarta, and was aimed to know the influence ofthe use of the filtration series in decreasing turbidity and coliform by employing a pre-test posttest with control group designed experiment. The rainwater sample was collected by using integrated sampling method from five collection points, and the subsequent examination of turbidityand coliform were conducted in the Health Laboratory Office of Yogyakarta. Between each replications, in order to clean the filtration mediums, the series were washed before be used again.The results showed that after the data were tested by using multivariate anova (manova), it wasfound that the aggregated p value was <0.05, meaning that the filration process was significantin declining both the turbidity level and coliform number between the treatment and controlgroups. In the treatment group the turbidity and coliform decreased as much as 68,17 % and95,11 %, respectively.